Cinematic Independence Constructing the Big Screen in Nigeria - Tsika, Noah (University of California Press, 2022)
Cinematic Independence traces the emergence, demise, and rebirth of big-screen film exhibition in Nigeria. Film companies flocked to Nigeria in the years following independence, beginning a long history of interventions by Hollywood and corporate America. The 1980s and 1990s saw a shuttering of cinemas, which were almost entirely replaced by television and direct-to-video movies. However, after 1999, the exhibition sector was revitalized with the construction of multiplexes. Cinematic Independence is about the periods that straddle this disappearing act: the immediate decades bracketing independence in 1960, and the years after 1999. At stake is the Nigerian postcolony's role in global debates about the future of the movie theater. That it was eventually resurrected in the flashy form of the multiplex is not simply an achievement of commercial real estate, but also a testament to cinema's persistence-its capacity to stave off annihilation or, in this case, come back from the dead.